GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 63608 species occurrences available in GBIF matching the query: TaxonKey: Canis lupus Linnaeus, 1758 HasGeospatialIssue: false HasCoordinate: true. The dataset includes 63608 records from 231 constituent datasets: 11133 records from OEH Atlas of NSW Wildlife. 3 records from MSB Mammal Observations (Arctos). 1 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 111 records from MVZ Mammal Collection (Arctos). 2176 records from Australian National Wildlife Collection provider for OZCAM. 3 records from PlutoF platform observations. 1 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 646 records from BioGIS - Mammals - INPA database. 69 records from KUBI Mammalogy Collection. 95 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 1105 records from Inventario Español de Especies Terrestres (MAGRAMA). 11 records from CUMV Mammal Collection (Arctos). 1956 records from Fauna Atlas N.T.. 1773 records from UAM Mammal Collection (Arctos). 89 records from Museum Victoria provider for OZCAM. 382 records from Cowan Tetrapod Collection - Mammals. 504 records from Arctic Species Trend Index (ASTI) : Terrestrial. 27975 records from Inventaire National du Patrimoine Naturel : Loup en France. 2367 records from SA Fauna (BDBSA). 140 records from Field Museum of Natural History (Zoology) Mammal Collection. 4 records from Lund Museum of Zoology (MZLU). 391 records from Données ONF Faune-Flore-Fonge. 14 records from CHAS Mammalogy Collection (Arctos). 5646 records from Norwegian Biodiversity Information Centre - Other datasets. 9 records from Museum of Comparative Zoology, Harvard University. 5 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 61 records from iNaturalist Research-grade Observations. 23 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 14 records from Mammals housed at MHNG, Geneva. 10 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 16 records from NMNH occurrence DwC-A. 285 records from BioGIS - Mammals - SPNI. 36 records from DMNS Mammal Collection (Arctos). 59 records from Mammal collection, Natural History Museum, University of Oslo. 1158 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 1 records from Colección de mamíferos de la Universidad del Valle. 29 records from naturgucker. 27 records from CAS Mammalogy (MAM). 82 records from UMMZ Mammal Collection. 12 records from BioGIS - Hamaarag. 12 records from MfN - Fossil vertebrates IV. 21 records from Mammal Collection. 6 records from SBMNH Vertebrate Zoology. 31 records from Northern Territory Museum and Art Gallery provider for OZCAM. 38 records from LACM Vertebrate Collection. 2 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 235 records from Western Australian Museum provider for OZCAM. 10 records from Natural History Museum (London) Collection Specimens. 57 records from Macaulay Library Audio and Video Collection. 3 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 1 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 2 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 1 records from Akita Prefectural Museum＋Mammalians Specimens of Akita Prefectural Museum. 3 records from RBINS collections. 1 records from ISU Mammals. 21 records from UWBM Mammalogy Collection. 8 records from NYSM Mammals. 17 records from LSUMZ Mammals Collection. 79 records from Paleobiology Database. 7 records from Individual Sightings. 1 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 65 records from Mammals Specimens. 2 records from FHSM Mammals Collection. 10 records from CNMA/Colección Nacional de mamíferos. 16 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 7 records from TTU Mammals Collection. 963 records from Israel Nature and Parks Authority. 305 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 2 records from UCLA Donald R. Dickey Bird and Mammal Collection. 17 records from inatura - Erlebnis Naturschau Dornbirn. 38 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 6 records from Occurrence of mammalia relicts at site Lespezi-Lutarie. 8 records from Occurrence of mammalia relicts at site Pestera Cioarei. 1 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 9 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 2 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 3 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 2 records from Occurrence of mammalia relicts at site Malerfels_I. 9 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 5 records from Occurrence of mammalia relicts at site Bocksteingrotte/Lonetal. 10 records from Occurrence of mammalia relicts at site Raj Cave. 2 records from Occurrence of mammalia relicts at site Castlepook Cave. 4 records from Occurrence of mammalia relicts at site L´Abri Duruthy. 2 records from Occurrence of mammalia relicts at site la Grotte du Thai. 3 records from Occurrence of mammalia relicts at site Tornewton Cave. 1 records from Occurrence of mammalia relicts at site Picken´s Hole. 1 records from Occurrence of mammalia relicts at site Kesslerloch. 1 records from Occurrence of mammalia relicts at site Rislisberghöhle. 1 records from Occurrence of mammalia relicts at site Stellmoor. 6 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 24 records from Occurrence of mammalia relicts at site Brillenhöhle. 1 records from Occurrence of mammalia relicts at site Villa Seckendorff. 5 records from Occurrence of mammalia relicts at site Krapina. 3 records from Occurrence of mammalia relicts at site Koziarna Cave. 2 records from Occurrence of mammalia relicts at site Sveduv stul. 9 records from Occurrence of mammalia relicts at site Pod hradem. 5 records from Occurrence of mammalia relicts at site Geißenklösterle. 6 records from Occurrence of mammalia relicts at site Veternica. 14 records from Occurrence of mammalia relicts at site Velika Pecina. 2 records from Occurrence of mammalia relicts at site Vindija. 2 records from Occurrence of mammalia relicts at site Sandalja II. 2 records from Occurrence of mammalia relicts at site Kalman Lambrecht Cave. 1 records from Occurrence of mammalia relicts at site Subalyuk. 1 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 3 records from Occurrence of mammalia relicts at site Pilisszanto 1. 3 records from Occurrence of mammalia relicts at site Remetehegy. 1 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 1 records from Occurrence of mammalia relicts at site Felsställe. 1 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 1 records from Occurrence of mammalia relicts at site Bettelküche. 1 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 2 records from Occurrence of mammalia relicts at site Wallertheim. 2 records from Occurrence of mammalia relicts at site Stematia. 1 records from Occurrence of mammalia relicts at site Barrington. 1 records from Occurrence of mammalia relicts at site Willments Pit. 1 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 1 records from Occurrence of mammalia relicts at site Gönnersdorf. 1 records from Occurrence of mammalia relicts at site Kartstein. 4 records from Occurrence of mammalia relicts at site Moladova V. 6 records from Occurrence of mammalia relicts at site Sirgenstein. 1 records from Occurrence of mammalia relicts at site Ettingen. 1 records from Occurrence of mammalia relicts at site la Grotte des Fees. 1 records from Occurrence of mammalia relicts at site le Roc de Marcamps. 3 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 3 records from Occurrence of mammalia relicts at site Nietoperzowa. 1 records from Occurrence of mammalia relicts at site Wretton. 1 records from Occurrence of mammalia relicts at site Lehringen. 4 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 7 records from Occurrence of mammalia relicts at site l´Abri de la Madeleine. 2 records from Occurrence of mammalia relicts at site la Grotte Maldidier. 4 records from Occurrence of mammalia relicts at site l´Abri du Morin. 5 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Ouest. 6 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 3 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 7 records from Occurrence of mammalia relicts at site Roc de Combe. 1 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1 records from Occurrence of mammalia relicts at site Kirkdale Cave. 1 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 1 records from Occurrence of mammalia relicts at site Crayford. 1 records from Occurrence of mammalia relicts at site Kugelsteinhöhle II. 1 records from Occurrence of mammalia relicts at site Dendermonde. 1 records from Occurrence of mammalia relicts at site Rotselaar. 2 records from Occurrence of mammalia relicts at site Zemst Bos van A. 3 records from Occurrence of mammalia relicts at site Goyet Cave 3. 1 records from Occurrence of mammalia relicts at site Dolni Vestonice. 1 records from Occurrence of mammalia relicts at site Barova Cave. 1 records from Occurrence of mammalia relicts at site Adler Cave xx. 1 records from Occurrence of mammalia relicts at site Pavlov. 4 records from Occurrence of mammalia relicts at site Wildenscheuer Cave. 1 records from Occurrence of mammalia relicts at site Ochoz Cave. 9 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 2 records from Occurrence of mammalia relicts at site Kniegrotte. 7 records from Occurrence of mammalia relicts at site Sirgenstein Cave. 1 records from Occurrence of mammalia relicts at site Klithi. 4 records from Occurrence of mammalia relicts at site Hunas. 1 records from Occurrence of mammalia relicts at site Risovaca. 3 records from Occurrence of mammalia relicts at site Zawalona Cave. 1 records from Occurrence of mammalia relicts at site Oelknitz. 1 records from Occurrence of mammalia relicts at site Predmosti. 2 records from Occurrence of mammalia relicts at site Smolucka Pecina. 1 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 1 records from Occurrence of mammalia relicts at site Oberkassel bei Bonn. 3 records from Occurrence of mammalia relicts at site Teufelsbrücke. 1 records from Occurrence of mammalia relicts at site Vraona Cave. 8 records from Occurrence of mammalia relicts at site Pestera Cioarei. 2 records from Herdengelhoehle taxa and datings. 1 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 1 records from Occurrence of mammalia relicts at site Erdhöhle. 1 records from Occurrence of mammalia relicts at site Niederlehme. 1 records from Occurrence of mammalia relicts at site Buchenloch. 1 records from Occurrence of mammalia relicts at site Kogelstein. 2 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 8 records from Occurrence of mammalia relicts at site Grotte Scladina. 2 records from Occurrence of mammalia relicts at site Pestera Magura. 1 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 1 records from Occurrence of mammalia relicts at site Sernesul Rece Cave. 2 records from Occurrence of mammalia relicts at site Igrita Cave. 1 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 1 records from Occurrence of mammalia relicts at site Valea Sesii Cave. 3 records from Occurrence of mammalia relicts at site Pestera Livadita. 3 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 6 records from Occurrence of mammalia relicts at site Pestera la Adam. 1 records from Occurrence of mammalia relicts at site Pestera Hotilor. 1 records from Occurrence of mammalia relicts at site Erbiceni. 1 records from Occurrence of mammalia relicts at site Icoana. 2 records from Occurrence of mammalia relicts at site Schweizerbild. 2 records from Occurrence of mammalia relicts at site Großes Schulerloch. 2 records from Occurrence of mammalia relicts at site Fuchsenloch. 3 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1 records from Occurrence of mammalia relicts at site Große Ofnethöhle. 1 records from Occurrence of mammalia relicts at site Grotte de la Martine. 3 records from Occurrence of mammalia relicts at site Einhornhöhle. 4 records from Occurrence of mammalia relicts at site Climauti II. 8 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 2 records from Occurrence of mammalia relicts at site Felsställe. 89 records from PSM Vertebrates Collection. 2 records from Coleccion de sonidos ambientales. 6 records from UAZ Mammals. 176 records from Biological and palaeontological collection and observation data MNHNL. 9 records from UAM Earth Sciences Collection (Arctos). 17 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 21 records from Mammal Specimens. 9 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 74 records from Terrestrial vertebrates. 201 records from Queensland Museum provider for OZCAM. 11 records from BioGIS - Mammals - HUJ collections. 58 records from Geographically tagged INSDC sequences. 1 records from Fieldjournal.org observation database. 5 records from Norwegian Species Observation Service. 268 records from MSB Mammal Collection (Arctos). 187 records from MSB Host Collection (Arctos). 6 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from Animal Sound Archive. 286 records from Mammalogy Collection - Royal Ontario Museum. 487 records from Estonian Nature Observations Database. 96 records from Large mammals in Israel from camera traps. 1 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 391 records from Données ONF Faune-Flore-FOnge. 16 records from National System of Protected Areas in Poland - Animals. 241 records from Australian Museum provider for OZCAM. 11 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 2 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 2 records from Anymals+plants - Citizen Science Data. 21 records from NCSM Mammals Collection. 58 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 1 records from Collection Mammalogie - ZSRO. 3 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 52 records from South Australian Museum Australia provider for OZCAM. 27 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences